Implementasi Electronic Customer Relationship Management (E-CRM) untuk Meningkatkan Layanan Pelanggan Belig Coffee - Ilyas, Aldrin Nur; Hin, Lauw Li; Sutrisno, Joko; Rusdah, Rusdah (Universitas Indraprasta PGRI Jakarta, 2024)
Belig Coffee is a culinary business that sells a variety of coffee drinks and snacks. Belig Coffee wants to establish a good relationship with its customers but there are still problems that exist, namely that currently the cafe does not have an online table booking system for customers to book tables and then in recording menu order transactions, customers still use paper to view the menu and order menus. With these problems, the solution presented is to create a CRM website using the PHP (Hypertext Preprocessor) programming language, codeigniter 3 framework, and using the MySql database. There are online table booking features, dine in reservations and online payment features that can facilitate customers in making order transactions and then with the menus displayed through the website so that customers can easily see the available menus and promos provided. With this CRM website, it is hoped that the cafe can improve good relations and improve service quality to customers.